Letramento e inclusão escolar – uma pesquisa colaborativa com professoras de uma escola pública - Rosa, Silvia Rodrigues (2020)
The study developed aimed at discussing literacy (KLEIMAN, 1995, 2008; SOARES, 2001, 2009, 2011, 2018; STREET, 2014, among others) and school inclusion (DENARI, 2006; MANTOAN, 2003, 2009, 2012, 2019; SANTOS; REIS; 2016; SKLIAR, 2006, among others) with Elementary School teachers – early years of a public school, which is located in Aparecida de Goiânia, through a collaborative experience of continuing teacher education (IBIAPINA, 2008, 2012; IMBERNÓN, 2009; WENGZYNSKI; TOZETTO, 2012, among others). The discussions built in this work focus on literacy and school inclusion aiming at classroom assistance for students with Special Educational Needs (SEN). In this process, the classroom and the school are regarded as spaces for social practices, in which teachers and students are active agents of their realities. The research is qualitative (BORTONI-RICARDO; CELANI, 2003; DENZIN; LINCOLN, 2009, 2013; FLICK, 1992; TRIVIÑOS, 1987, among others) and was developed by a group of four teachers and me from May to December 2019. During the study, the activities comprehended reading and discussing ten academic texts as well as problematizing the teaching-learning process of literacy and school inclusion in the light of these texts. Thus, the objectives of the study were to: 1) reflect upon the concepts and issues that involve literacy and school inclusion in a collaborative educational experience with Elementary School teachers – early years of a public school; 2) analyze and characterize how the group interprets a collaborative teacher education experience which focuses on literacy and school inclusion. In order to do this, the following sources of empirical material were used: an initial questionnaire, study group discussions on selected texts (recorded in audio and later transcribed), interviews (recorded in audio and later transcribed) and notes from the researcher´s diary. In relation to the teaching-learning process of literacy and school inclusion, the teachers focused on the discussion of their understandings on the perspective of education, in order to highlight their local realities, to question both the conflicts and the resolutions of problems experienced at school. In relation to teacher education, both teaching preparation and challenges for the implementation of a systematic work were highlighted, based on didactic actions for the implementation of literacy for the assistance of students with Special Educational Needs (SEN), the care related to their development and the difficulties and contributions of the research to the participating group.